Transmembrane mucin MUC1 overexpression and its association with CD10+ myeloid cells, transforming growth factor‐β1 expression, and tumor budding grade in colorectal cancer. Issue 7 (21st May 2013) - Khanh, Do Trong; Mekata, Eiji; Mukaisho, Ken‐ichi; Sugihara, Hiroyuki; Shimizu, Tomoharu; Shiomi, Hisanori; Murata, Satoshi; Naka, Shigeyuki; Yamamoto, Hiroshi; Endo, Yoshihiro; Tani, Tohru
Abstract : The prognostic value of mucin expression has been reported in several studies. We examined the association between mucin expression and other previously reported prognostic factors, including infiltration of CD10 + myeloid cells, transforming growth factor‐β1 (TGF‐β1) expression, and tumor budding at invasion fronts. Immunohistochemical analysis of 206 colorectal samples was carried out to determine whether MUC1, MUC2, MUC4, and MUC5AC expression could predict the survival of colorectal cancer patients. Serial sections were stained for CD10, TGF‐β1, and pan‐cytokeratin in order to detect tumor budding. As per multivariate analyses, MUC1 expression appeared to be the most significant predictor of both recurrence‐free survival and overall survival. MUC4 was only significant to predict recurrence‐free survival, and MUC5AC could be a good marker in stage IV colorectal cancers that require additional chemotherapy. MUC1 (CD227) expression was associated with infiltration of CD10 + myeloid cells, TGF‐β1 expression, and tumor budding grade. These findings suggest that MUC1 is indicative of poor prognoses that may be associated with immunosuppression and epithelial–mesenchymal transition. Furthermore, MUC1 expression appears to be a chemoattractant for CD10 + stromal cells.